Short‐term postoperative efficacy of steroid‐eluting stents for eosinophilic chronic rhinosinusitis with nasal polyps: A randomized clinical trial. Issue 5 (26th September 2022) - Wang, Chengshuo; Yu, Longgang; Chu, Xiaohan; Wang, Kuiji; Li, Jian; Lai, Yinyan; Meng, Cuida; Wen, Weiping; Zhu, Dongdong; Zhang, Yuan; Zhang, Luo
Abstract: Background: Eosinophilic chronic rhinosinusitis with nasal polyps (ECRSwNP) is a refractory clinical phenotype with a high symptom burden and relapse rate. Steroid‐eluting stents are safe and effective for reducing polyp size, symptom burden, and the need for revision sinus surgery. In this study we aimed to evaluate the efficacy and safety of steroid‐eluting stent implantation on the surgical outcomes of patients with ECRSwNP. Methods: This prospective, multicenter, randomized, intrapatient‐controlled trial recruited patients 18 to 65 years of age with ECRSwNP who required surgery. Ninety‐eight patients were enrolled and randomly implanted with absorbable steroid‐eluting stents containing mometasone furoate in one sinus at the end of surgery. All patients received standard postoperative care and follow‐up. The primary outcome was the Lund‐Kennedy endoscopic score within 12 weeks postsurgery. Secondary outcomes included nasal symptoms scores, nasal resistance, acoustic rhinometry, nasal nitric oxide levels, 3‐dimensional volumetric computed tomography scores, and eosinophil counts in the ethmoid mucosa. Results: Ninety‐five patients completed the trial. At postoperative weeks 4, 8, and 12, the Lund‐Kennedy scores were significantly lower on the treatment side than on the control side (all p  < 0.01). Compared with the treatment side, the control side exhibited higher tissue eosinophilia at week 4 and higher volumetric, nasal obstruction, and total nasal symptom scores at postoperative week 8 ( p  = 0.011, p  = 0.011, p  < 0.01, and p  = 0.001, respectively). No adrenal cortical suppression or serious side effects were observed. Conclusion: Steroid‐eluting stents reduce postoperative sinus mucosal edema, and eosinophilic inflammation, with persistent effects after stent disintegration, and are a good supplementary postsurgical treatment in patients with ECRSwNP.